2010
DOI: 10.1152/ajpheart.00959.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aldehyde dehydrogenase mediates vasodilator responses of glyceryl trinitrate and sodium nitrite in the pulmonary vascular bed of the rat

Abstract: PJ. Mitochondrial aldehyde dehydrogenase mediates vasodilator responses of glyceryl trinitrate and sodium nitrite in the pulmonary vascular bed of the rat. Am J Physiol Heart Circ Physiol 299: H819 -H826, 2010. First published June 11, 2010; doi:10.1152/ajpheart.00959.2009.-It has been reported that mitochondrial aldehyde dehydrogenase (ALDH2) catalyzes the formation of glyceryl dinitrate and inorganic nitrite from glyceryl trinitrate (GTN), leading to an increase in cGMP and vasodilation in the coronary and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…76 In contrast, antihypertensive molecules, such as Amyl Nitrite, are known to be ALDH2 agonists with vasodilator effects. 77 Twenty-seven of the 72 genes we identified have no prior support in hypertension and can, therefore, be considered as novel hypertension candidates. Six of these novel candidate genes are potentially druggable, determined using the Chembl database; https://www.ebi.ac.uk/chembl/.…”
Section: Pathway Analysis As a Tool To Explore The Therapeutic Potentmentioning
confidence: 98%
“…76 In contrast, antihypertensive molecules, such as Amyl Nitrite, are known to be ALDH2 agonists with vasodilator effects. 77 Twenty-seven of the 72 genes we identified have no prior support in hypertension and can, therefore, be considered as novel hypertension candidates. Six of these novel candidate genes are potentially druggable, determined using the Chembl database; https://www.ebi.ac.uk/chembl/.…”
Section: Pathway Analysis As a Tool To Explore The Therapeutic Potentmentioning
confidence: 98%
“…ii) systemic vasoconstriction, using an intravenous infusion of norepinephrine at a rate of 1.5 µg/kg/min iii) NOS inhibition, where animals received a 1.5 mg/kg/min infusion of the potent, nonselective NOS inhibitor S-ethyl-isothiourea (SEITU) (Southan et al, 1995); iv) nitrite (NO 2 -) administration, where animals received a 250 µg/kg/min infusion of sodium nitrite, NaNO 2 (Badejo et al, 2010); v) a combination of NOS inhibition with SEITU, and NaNO 2 administration (doses as above); vi) non-haem NO scavenging, using an infusion of the scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide (C-PTIO) (Yoshida et al, 1994) running at 0.17 mg/kg/min;…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…17) Similarly, it is reported that the vasodilatory effects of GTN and NO 2 − on pulmonary and systemic vascular beds of anesthetized rats were attenuated by cyanamide, while the inhibitor had no effect on SNP-induced vasodilation. 18) The doses of GTN used in the above studies correspond to the middle dose (about 10 µg/kg) that used in the present in vivo study. However, no direct comparison between GTN and ISDN in vivo with an ALDH2 inhibitor has been reported previously, although cyanamide has been used clinically for many years.…”
Section: Discussionmentioning
confidence: 95%